Keefektifan Konseling Kelompok Cognitive Behavior dengan Teknik Cognitive Restructuring untuk Mereduksi Kecanduan Game Online pada Peserta Didik SMP Muhammadiyah Bantul - Intan Nur Cahyani; Akhmad Fajar Prasetya (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2026)
This study is grounded in the observation that online game addiction has emerged among learners at SMP Muhammadiyah Bantul. In the present digital era, playing games through the internet has become tightly woven into adolescents' everyday routines. Easy accessibility together with the broad spectrum of entertainment provided has pushed the popularity of online games upward. However, immoderate engagement may foster addictive patterns that adversely affect students' academic performance, social interaction, physical condition, and mental well-being. Hence, a workable intervention is required to lower the level of dependence. The purpose of this research is to decrease learners' online game addiction by means of group counseling services that draw on the Cognitive Behavioral Therapy (CBT) framework combined with cognitive restructuring techniques. A one-group pretest-posttest experimental scheme was adopted in this work. The findings reveal a notable reduction in the students' online game addiction scores, evidenced by the paired sample t-test significance value (two-tailed) of 0.000, which falls below 0.05. It can therefore be inferred that group counseling rooted in the Cognitive Behavioral Therapy approach with cognitive restructuring techniques is effective for reducing online game addiction in seventh-grade learners at SMP Muhammadiyah Bantul.